I2SPhybrid pulse shape: Modified I2SP pulse by using weighting technique and it’s impact on SC-FDMA system - Bhandari, G; Vijay, S (International Journal of Computer Sciences and Engineering, 2025)
Pulse shaping plays a crucial role in spectral shaping in the modern wireless communication to reduce the spectral bandwidth. Pulse shaping is a spectral processing technique by which fractional out of band power is reduced for low cost, reliable, power and spectrally efficient mobile radio communication systems. The Multipath channel has two main considerations spectral efficient transmission and reduced ISI both these requirement of Spectral efficient transmission and reduced ISI are satisfied by pulse shaping the transmitted signal. I2SPhybrid pulse shape introduced in this research work by using weighting techniques has better spectral characteristics and shows improved OBR performance when used with SC-FDMA system.